1999
DOI: 10.3171/jns.1999.90.5.0875
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of cotransplantation of peripheral nerve and adrenal medulla in patients with Parkinson's disease

Abstract: Implantation of tissue other than fetal tissue can promote a long-term improvement in the clinical symptomatology of seriously disabled parkinsonian patients. This finding is supported by the autopsy report of a patient with PD who had undergone grafting of AM plus peripheral nerve in which it was demonstrated that a large number of tyrosine hydroxylase-positive cells survive 1 year after implantation. In addition, there was a dense network of host dopaminergic fibers around the graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Moreover, this occurs to a similar extent in both normal and MPTP‐treated animals (Howells, unpublished observation). Similar dopaminergic sprouting is also observed in human PD patients after implantation of fetal mesechephalon or autologous adrenal medulla into the striatum15–18 and may contribute to the moderate clinical benefit seen even in patients with poor graft survival 15, 16…”
mentioning
confidence: 70%
“…Moreover, this occurs to a similar extent in both normal and MPTP‐treated animals (Howells, unpublished observation). Similar dopaminergic sprouting is also observed in human PD patients after implantation of fetal mesechephalon or autologous adrenal medulla into the striatum15–18 and may contribute to the moderate clinical benefit seen even in patients with poor graft survival 15, 16…”
mentioning
confidence: 70%
“…In this respect, co-grafting of adrenal medulla and pretransected peripheral nerve was found to promote both graft survival and functional recovery in animal models of PD [23,24]. This has been further explored in clinical trials and reported to show some gradual and significant alleviation of PD symptoms with modest improvement of UPDRS scores in both the "on" and "off" phases as well as prolonging the duration of the "on" phases with a concomitant reduction in the "off" time [25][26][27][28][29]. However, the size of the clinical benefit is modest and this, coupled to a loss of efficacy over time, has limited its applicability.…”
Section: Adrenal Medullamentioning
confidence: 91%
“…Despite initial enthusiasm after the early efforts at adrenal medulla autografts for PD [25], within a short time the grafts were shown to be no better than therapy with available dopamine agonists [26]. Some have continued to autograft adrenal medulla tissue with the addition of nerve growth factor that is infused or provided by peripheral nerve co-grafts [27,28]. An open-label study found benefi t in six patients with PD after dopamineproducing autologous carotid body cells were transplanted [29].…”
Section: Other Cell Types For Dopamine Replacementmentioning
confidence: 96%